\(a,\left(4-xy\right)^3\)
\(=4^3-3.4^2xy+3.4.x^2y^2-x^3y^3\)
\(=64-48xy+12x^2y^2-x^3y^3\)
\(b,\left(0,1+xy\right)^3\)
\(=\left(0,1\right)^3+3.\left(0,1\right)^2xy+3.0,1.\left(xy\right)^2+x^3y^3\)
\(=0,001+0,03xy+0,3x^2y^2+x^3y^3\)
\(a,\left(4-xy\right)^3\)
\(=4^3-3.4^2xy+3.4.x^2y^2-x^3y^3\)
\(=64-48xy+12x^2y^2-x^3y^3\)
\(b,\left(0,1+xy\right)^3\)
\(=\left(0,1\right)^3+3.\left(0,1\right)^2xy+3.0,1.\left(xy\right)^2+x^3y^3\)
\(=0,001+0,03xy+0,3x^2y^2+x^3y^3\)
viet cac bieu thuc sau duoi dang tong:
a,(-3x+2)\(^3\)
viet cac bieu thuc sau duoi dang tong:
a,(-3x+2)\(^3\)
viet cac bieu thuc sau duoi dang tich: x^3 y^3+225
viet cac bieu thuc sau duoi dang tich:
a, -64+(x-3)\(^3\)
viet cac bieu thuc sau duoi dang tich:
a, -64+(x-3)\(^3\)
viet cac bieu thuc sau duoi dang tich:
b,(a-1)\(^3\)-(a+1)\(^3\)
viet cac bieu thuc sau duoi dang tich;
a,x\(^3\)y\(^3\)+225
viet cac bieu thuc sau duoi dang tich:
b,(a-1)\(^3\)-(a+1)\(^3\)
viet cac bieu thuc sau duoi dang tich:
a, a\(^6\)-b\(^6\)